Bernardo Guimarães, social thinker - Luciano Mendes de Faria Filho (Revista Brasileira de História da Educação, 2012)
Bernardo Guimarães, literary work synthesizes more a disorganized and incoherent complex of themes, projects and visions of world that were part of the intellectual, political and cultural environments experienced by the author than an organized project. In this study, I will devote an effort aiming at elucidating how Bernardo Guimarães presents his narrators and characters establishing their routines and refl ecting about major and minor political and social concerns that surrounded him, such as violence, family relationships, slavery, indigenous and civility problematics and the relationships between the urban area and rural area.